Towards Comprehensive Information Security Awareness: A Systematic Classification of Concerns among University Students - Ali Farooq; Shamil Alifov; Seppo Virtanen; Jouni Isoaho (United Kingdom, 2022)
In this paper, we have systematically identified and classified information security concerns (ISCs) of university students into areas where users perceive information security threats. 354 university students were asked to elicit their level of concern on a given set of 74 ISCs using a 7-point scale. Factor analysis (PCA) produced an 11-factor solution, each factor depicting an area of concern. These areas were related to Personal (legal awareness), Social (Sociality), Institutional (Staff member lapses, University networks), Technological (Online social network use, Intrusive service providers, Web browsing and email, Smartphone use, Electronic device use, and Conventional threats), and Non-technological (Cards and wallets security) aspects of student’s day-to-day life. The majority of the students (66%) showed concerns related to online social network use, whereas, only 40% of them shown concerns related to sociality. The highest level of concerns was related to service providers, whereas the lowest level of concerns was related to sociality
Proceedings of the 32nd International BCS Human Computer Interaction Conference (HCI 2018)